Father J.M. Mouchet - Coates, Kenneth S. (ARCTIC, 1989)
"Motivation!" That single word, spoken with a strong French accent and remarkable conviction, resonates in the ears of hundreds of northern Canadian cross-country skiers, past and present. The speaker, Father J.M. Mouchet, O.M.E., played an instrumental role in introducing the sport to the North in the 1960s. His remarkable dedication and enthusiasm for cross-country skiing - for the North, and for the Native people - has left a mark on the entire region. . Always an active sportsman, Mouchet was very impressed with the Natives' physical fitness, which he attributed to their active lifestyle and adaptation to their environment. He further believed that the Natives faced tremendous social and economic changes as a result of th expansion of non-Native society in the North. Physical achievement through cross-country skiing, he believed, offered Native children the self-esteem and the physical and mental toughness to deal with rapidly changing times. Mouchet put these ideas into action. He organized cross-country skiing teams in Old Crow and, with the assistance of others who shared his vision, in Inuvik. The Native participants in the Territorial Experimental Ski Training (TEST) Programme proved the correctness of his vision. A number of the skiers that he brought into the sport became members of Canada's national ski team; the Firth sisters, Sharon and Shirley, are examples. Native skiers dominated skiing competitions throughout the North for a number of years. . Mouchet moved his training scheme to Whitehorse, where it was introduced into the elementary school system. From modest beginnings - with seven pairs of skis at Takhini Elementary - the cross-country ski training program became one of the most popular participation sports in the territory. . Father Mouchet now resides in Whitehorse. He continues to be active in cross-country skiing, showing the same dedication and encouragement that he first brought to the Canadian North over forty years ago. .